On the “Periphery” of the Neolithic: hunter-gatherers of Europe - Ekaterina V. Dolbunova; Andrey N. Mazurkevich (Археология евразийских степей)
The article discusses the main components, determining the neolithization process of Eastern Europe, i.e. paleoclimatic triggers, distribution of archaeological cultures and innovations, the appearance of the first pottery as a fundamental criterion, reflecting changes within hunter-gatherer communities and modeling the chronology of this process. The first results of multivariate statistical analysis of Early Neolithic pottery assemblages of Eastern Europe are presented. Special attention is paid to the discussion of hunter-gatherer pottery in Northern, Central, and Western Europe. The study of the latter indicates different ways of origin of various cultures, as well as fundamental differences between them. The discussion of models, created for the Early Neolithic, the introduction of archaeological information suggests the existence of cultural and natural boundaries that may have delayed or accelerated the spread of different innovations and new populations, as well as a mechanism for the spread of pottery as an innovation in which knowledge of the functional use/content of vessels was transmitted as a single package together with traditions in technology, decor and morphology.